Pore Structures and Abrasion of Concrete Containing Crumb Rubber from Scrap Tyre as a Partial Replacement to Fine Aggregate - Perumal, Nyanambkai (Universiti Teknologi PETRONAS, 2017)
Crumb rubber concrete (CRC) displays various advantages contrasted with conventional concrete, for example, low density, higher ductility, enhanced plastic limit, higher durability, higher impact resistivity, low thermal conductivity, better sound absorption and better electrical resistivity. However, the primary disadvantages of CRC which prevents its utilization in construction field is the low compressive strength. So, to enhance the properties of the CRC, the pozzolonic material such fly ash and nanosilica was added in the CRC mixture. Using Response Surface Methodology (RSM), thirty trial mixtures with three levels of crumb rubber (0%, 15%, 30%) replacement by volume to fine aggregate, three levels of nano silica (0%, 2.5%, 5%) addition by weight of cementitious material, three levels of fly ash (0%, 35%, 70%) addition by weight and three level of water/cement ratio (0.25,0.30,0.35) were prepared and tested for compressive strength of CRC after curing of 14 days and 28 days to find the optimum mix design. The compressive strength result was used in Analysis of Variance (ANOVA) process in RSM to develop six mixtures that can achieve desirable strength of M20, M25, M30, M40, M50 and M60